2023
DOI: 10.3390/diagnostics13091619
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genomic Profiling and Therapeutic Implications for Patients with Advanced Cancers: The Experience of an Academic Hospital

Abstract: Next-generation sequencing (NGS) can be used to detect tumor-specific genomic alterations. This retrospective single-center study aims to assess the application of an extensive NGS panel to identify actionable alterations and initiate matched targeted treatment for patients with advanced cancer. We analyzed genomic alterations in solid tumor biopsies from 464 patients with advanced cancer with the Foundation Medicine assay (FoundationOne®CDx). Therapeutic implications were determined using the Memorial Sloan K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The median age of the patients included in our study was 60.5 (range 27-82) years, which is similar to the median age of the population reported in different studies that analysed solid tumour samples with the Foundation Medicine ® platform [17][18][19][20]. A total of 72 samples were processed for the identification of genomic alterations, and data were obtained for 67 samples, corresponding to a success rate of 93.1%.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The median age of the patients included in our study was 60.5 (range 27-82) years, which is similar to the median age of the population reported in different studies that analysed solid tumour samples with the Foundation Medicine ® platform [17][18][19][20]. A total of 72 samples were processed for the identification of genomic alterations, and data were obtained for 67 samples, corresponding to a success rate of 93.1%.…”
Section: Discussionsupporting
confidence: 54%
“…Despite the presented data and the potential benefits that patients can gain following the development of precision oncology, most of the genomic alterations identified in this study have no direct match with currently approved drugs, as reported in other large series using the same test [17][18][19]. One such example in this study is the cancers of unknown primary, which presented KRAS alterations.…”
Section: Discussionmentioning
confidence: 57%
“…No significant differences in IPS were observed in PD1, ALT4, and PD1+ALT4 between the two groups ( Figure 9A )., indicating that patients with high TRIB3 expression cannot benefit from PD1 and ALT4 ICP inhibitor treatments. However, the TMB analysis indicated that the high TRIB3 expression group was significantly higher than the low expression group ( Figure 9B ), implying that high TRIB3 expression patients have better immune responses ( 34 ). Therefore, to explore potential immune targets, a correlation analysis between TRIB3 and 47 well-known ICP genes was carried out ( 12 ).…”
Section: Resultsmentioning
confidence: 98%
“…), has been reported at various frequencies between 10% and 20% in all patients in Japan (5-7). Conversely, these cases have higher frequency overseas than that in Japan; however, the usefulness of multi-CGP testing remained not fully clarified (8,9) in Japan. In this study, we analyzed clinical data from multi-CGP testing in various solid cancers to clarify the significance of multi-CGP testing at our Hospital.…”
mentioning
confidence: 98%